Hotspots de atropelamentos e a influência da paisagem na sobrevivência de mamíferos de médio e grande porte em uma área do cerrado mineiro - Guimarães, Juliane Fernandes (2017)
Roadkill of wild vertebrates are among the greatest negative impacts from linear ventures, being a direct cause of biodiversity decline and environmental quality. In addition to wildlife-related accidents, highways play an important role in environmental degradation, as they favor human exploration in previously remote areas. The environmental impacts of the projects installed in the vicinity of the roads, operate in a synergistic and cumulative manner on the environment, contributing to the high mortality rates of wildlife through road accidents. Fauna passages are among the most efficient mitigation measures for the prevention of road accidents. The present study had as objective to analyze road-kills of the medium and large mammals on the highway BR-497, between the municipalities of Uberlândia and Prata, MG, and to characterize the uses and occupation of the ground in the surroundings of the linear enterprise through images, indicating measures that help In the reduction of mortality of wildlife individuals by trampling. The data of the run-offs were collected monthly from July 2015 to July 2016. There were 49 individuals distributed in 16 species, including three species under threat of extinction, the maned wolf (Chrysocyon brachyurus), anteater (Myrmecophaga tridactyla) and field fox (Lycalopex vetulus). The hotspots analyzed evidenced three nuclei with a higher incidence of accidents, which means that it is necessary to implement mitigation measures with the capacity to minimize the observed mortality, suggesting in this case the installation of structures that act as fauna overpass. In this study the landscape was analyzed by means of remote sensing with satellite image (LANDSAT 8), being supervised classification of use and occupation of the soil through the algorithm Maximum Likelihood, resulting in a percentage of anthropic use of approximately 80.00% .The analysis of the percentages of native vegetation was made through the construction of vegetation masks and buffers away from the central axis of the highway (1, 9 and 18 km), evidencing that the totals of natural remnants tend to reduce as the approach of the highways . In relation to trampling involving endangered fauna, considering the limits of their living areas, the results show that individuals suffer from strong environmental pressures, since a large part of the area necessary to establish their biological and ecological functions is under Anthropic use. In addition, the analysis for the remnants present in the study area, showed that the fragments classified as large (<4 km²) are scarce and are strongly influenced by environmental disturbances. Thus, in the current scenario, the conservation of species, mainly of medium and large mammals, that generally require large areas for the maintenance of their activities, depends directly on the establishment of goals that promote the connectivity and quality of habitats and of measures that minimize roadkill of wild life mortality on the BR-497 highway. In this sense, the present study may serve as a data base assisting in the conservation strategy for wild mammals of medium and large size present in the study region.